Research Article Screening of Plant Extracts for Antifeedant Activity Against Spodoptera litura and Helicoverpa armigera (Lepidoptera: Noctuidae). Issue 1 (2018) - Chinnamani, T.; Jeyasankar, A.
No abstract available